2005
DOI: 10.1002/hup.693
|View full text |Cite
|
Sign up to set email alerts
|

A review of the possible relevance of inositol and the phosphatidylinositol second messenger system (PI‐cycle) to psychiatric disorders—focus on magnetic resonance spectroscopy (MRS) studies

Abstract: Myo-inositol is an important part of the phosphatidylinositol second messenger system (PI-cycle). Abnormalities in nerve cell myo-inositol levels and/or PI-cycle regulation has been suggested as being involved in the pathophysiology and/or treatment of many psychiatric disorders including bipolar disorder, major depressive disorder, panic disorder, obsessive-compulsive disorder, eating disorders and schizophrenia. This review examines the metabolism and biochemical importance of myo-inositol and the PI-cycle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 144 publications
(142 reference statements)
2
80
0
4
Order By: Relevance
“…Myo-inositol is believed to be an astroglial marker, suggesting an involvement of astrocytes in these findings (Brand et al, 1993;Haroon et al, 2009;Kim et al, 2005;Plitman et al, 2016). Taken together, these data indicate an association between inflammation and glutamate dysregulation in mood disorders including depression.…”
Section: Preclinical and Clinical Studies: Translational Relevancementioning
confidence: 54%
“…Myo-inositol is believed to be an astroglial marker, suggesting an involvement of astrocytes in these findings (Brand et al, 1993;Haroon et al, 2009;Kim et al, 2005;Plitman et al, 2016). Taken together, these data indicate an association between inflammation and glutamate dysregulation in mood disorders including depression.…”
Section: Preclinical and Clinical Studies: Translational Relevancementioning
confidence: 54%
“…A report of abovenormal mI in left parietal WM was contradicted by another report of normal values in parietal lobes. 40 There is evidence suggesting that alterations in brain mI may be associated with psychiatric disorders such as bipolar disorder and schizophrenia, 90 but most spectroscopy studies have reported normal mI concentrations in several brain regions in schizophrenic patients. 18,28,91,92 Hence, the verdict on mI abnormalities in schizophrenia awaits further study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the explanations for the mI increase may involve several mechanisms, the main source of brain mI derives from brain recycling of inositol-containing phospholipids that are tightly linked to membrane phospholipids and their metabolism (1)(2)(3)(4)(5)18). The effects of tDCS are thought to be partly mediated by changes in the biophysical properties of membranes (16).…”
Section: Discussionmentioning
confidence: 99%
“…Many biochemical and signaling pathways utilize mI. mI is the basic compound for the synthesis of inositol-containing phospholipids (2)(3)(4) and is involved in the cellular membrane-based second-messenger system, as well as in direct action on membranes (3,5). Myoinositol and its phosphorylated derivatives are components of the phosphoinositide (PI) pathway (2), and at least four pyrophosphorylated inositol phosphates have been identified in the brain.…”
mentioning
confidence: 99%